A connexin 26 mutation causes a syndrome of sensorineural hearing loss and palmoplantar hyperkeratosis (MIM 148350). Issue 1 (1st January 2000) - Heathcote, Kirsten; Syrris, Petros; Carter, Nicholas D; Patton, Michael A
Abstract : We report a missense mutation in the connexin 26 gene ( GJB2 ) in a family with an autosomal dominant syndrome of hearing loss and hyperkeratosis. The affected family members have high frequency, slowly progressive, bilateral, sensorineural hearing loss and palmoplantar hyperkeratosis. The mutation causes an amino acid substitution (G59A), which may disrupt a reverse turn in the first extracellular loop of connexin 26. Connexin 26 mutations have been reported in syndromes of deafness and palmoplantar keratoderma. These data provide additional evidence for the role of connexin 26 in syndromes of this type.